A vuestra disposición – en torno al uso pragmático del posesivo vuestro en eldiscurso corporativo hispanoamericano - Rocha Ochoa, Carlos; Schnitzer, Johannes (Studia Linguistica Romanica)
Previous research has evidenced the current use of the possessive vuestro as part of the paradigms of usted and ustedes in Argentina (Fontanella de Weinberg 1995-1996), Chile (Wagner 1996-1997), Uruguay (Bertolotti 2007, 2020) and Peru (Dankel & Gutiérrez Maté 2020, 2021). This paper starts from the hypothesis that vuestro serves as an alternative to the polysemic su in formal contexts. The study examines written business communication in Spanish American countries with the aim of checking the use of vuestro. A systematic search in company websites yielded more than seven hundred examples. The results show a strategic use of vuestro with both singular and plural referents in six countries and a progressively greater presence towards the Southern Cone.